О выражении отрицательной оценки именами существительными со значением лица - Лассан, Э. Р. (Kalbotyra, 1986)
The article deals with the problem of the componential structure of the meaning. The negative value can be explicated by the component “не”. There are three main groups of the agentive nouns. In the first group “не” belongs to the modal frame of the meaning. In the second one “не” is connected with the whole meaning. In the third group “не” is included in the component to cause “not to be”.